Africa Agriculture Adaptation Atlas - Rosenstock, Todd Stuart; Steward, Peter Richard; Ramirez Villegas, Julian Armando; Youngberg, Brayden; Vyas, Shalika; Achicanoy Estrella, Harold Armando; Muller, Lolita; Joshi, Namita; Mehrabi, Zia; Chilambe, Pedro Anglaze; Thornton, Philip Kenneth; Wood-sichra, Ulrike (2025)
The codebase used to build the main website (not the notebooks) for the Africa Agriculture Adaptation Atlas. The code is designed to be easily modified and customized for country-specific or thematic Atlas spin-offs, enabling rapid reuse across contexts, such as a country specific Atlas. The repository includes a Next.js web application, Docker container configuration for reproducible deployment, and integration with Sanity as a headless content management system. A baseline Sanity dataset is available upon request to support setup, customization, and content extension.